Political participation of young people in rural Eastern Germany: empirical findings, structural barriers, and policy implications - Fehser, Stefan; Tillmann, Frank; Reißig, Birgit (Frontiers in Political Science, 2025)
This article examines the structural conditions and barriers of youth participation in rural regions of Eastern Germany. Combining quantitative data from the AID:A 2023 survey and qualitative case studies from municipal youth parliaments, the study investigates how spatial disparities, infrastructural challenges, and institutional frameworks shape young people’s political engagement. The findings demonstrate that urbanity and age are decisive factors for politicization, while infrastructural deficits and a lack of binding participatory structures hinder sustainable youth participation in rural areas. The study emphasizes the need for targeted support measures, such as strengthening local youth organizations, improving mobility infrastructure, and fostering a culture of political recognition.